2012
DOI: 10.1016/j.foodchem.2012.04.099
|View full text |Cite
|
Sign up to set email alerts
|

Release of wine monoterpenes from natural precursors by glycosidases from Oenococcus oeni

Abstract: Highlights► Glycosidases of Oenococcus oeni are able to release terpenes from natural substrates. ► Bacterial glycosidases have a high capacity to release both primary and tertiary terpene alcohols. ► Both glucosidase and arabinosidase from O. oeni are more active in grape juice than glycosidases from Aspergillus niger. ► Riesling mash was treated with O. oeni glycosidases before alcoholic fermentation. ► Wines produced with the glycosidases from O. oeni received positive ratings by a professional panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 37 publications
1
38
0
3
Order By: Relevance
“…Four O. oeni isolates retained their enzymatic activity under the conditions of winemaking. In a similar study, cell-bound glucosidase and arabinosidase activities from O. oeni strains released high levels of monoterpenes from natural substrates under optimal conditions [42]. The enzymes showed broad substrate specificities (release of both primary and tertiary terpene alcohols) and remained active in grape juice.…”
Section: Glycosidasesmentioning
confidence: 77%
“…Four O. oeni isolates retained their enzymatic activity under the conditions of winemaking. In a similar study, cell-bound glucosidase and arabinosidase activities from O. oeni strains released high levels of monoterpenes from natural substrates under optimal conditions [42]. The enzymes showed broad substrate specificities (release of both primary and tertiary terpene alcohols) and remained active in grape juice.…”
Section: Glycosidasesmentioning
confidence: 77%
“…Therefore, it seems to bear a certain irony that, in the context of enzymatic release of attractive wine aroma compounds from glycosylated precursors, we previously identified Lb. brevis as a versatile source of glycosidases (25,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…and Pediococci spp. (Guilloux-Benatier et al 1993;Grimaldi et al 2000Grimaldi et al , 2005bMichlmayr et al 2012b). Interestingly, a previous study reported that βG of SD-2a and 31MBR is an intracellular form and 31MBR possesses higher intracellular activity than SD-2a (Li et al 2012b).…”
Section: Resultsmentioning
confidence: 98%
“…The βG activity of both strains decreasing sharply at 45°C may be due to the damage caused by high temperature to intact cells, since an optimum temperature of 50°C has been observed for crude βG of the two strains (Li et al 2012b). Usually, pH is known as an important factor to affect the enzyme activity, especially low pH is considered as an inhibitor of βG activity (Grimaldi et al 2000;Michlmayr et al 2010bMichlmayr et al , 2012b.…”
Section: Resultsmentioning
confidence: 99%